(untitled) (Ustozlar uchun, 2025)
This article examines the fundamental goals and objectives of teachers in a modern classroom setting. It highlights academic aims such as developing foundational knowledge, fostering critical thinking, and supporting skill mastery. The article also explores teachers’ social–emotional, behavioral, professional, and instructional objectives, emphasizing their role in creating a positive learning environment, encouraging collaboration, instilling moral values, and promoting lifelong learning. The discussion demonstrates that teachers serve as mentors, guides, and facilitators whose influence extends beyond academic instruction and contributes significantly to students’ holistic development.